Performance of drought tolerant rice varieties in different altitudes at Duradada, Lamjung, Nepal - Dhakal, Sandesh; Adhikari, Bishnu Bilas; Kandel, Bishnu Prasad (Journal of Agriculture and Natural Resources, 2020)
To evaluate high yielding drought tolerant rice varieties in different altitudes, a field experiment was carried out at Duradanda, Lamjung, Nepal during rainy season of 2016 under rainfed condition. The experiment was laid out in a factorial randomized block design with two replications. The treatments comprised of six different rice varieties viz. Sukhadhan-1, Sukhadhan-2, Sukhadhan-3, Sukhadhan-4, Sukhadhan-5 and Sukhadhan-6 and four altitudes viz. 1000, 1200, 1400 and 1600 masl. The results revealed that rice variety Sukhadhan-2 produced the highest grain yield (2.93 t/ha) followed by Sukhadhan-5 (2.92 t/ha) and Sukhadhan-3 (2.82 t/ha). The highest grain yield of Sukhadhan-2 was due to higher number of effective tillers/m2 (228), higher number of grains/panicle (83), higher panicle length (21.79 cm) and low sterility percentage (27.91%) as compared to other varieties. Regarding to altitudes, the highest grain yield (3.34 t/ha) was obtained in lower altitude (1000 masl) followed by 1200 masl (2.79 t/ha), 1400 masl (2.68 t/ha and 1600 masl (1.85 t/ha). The lower yield in higher altitude was due to higher sterility percentage, less number of effective tillers per unit area and less number of effective grains per panicle. It seems that the performance of these varieties was good up to 1400 masl.